Randomised controlled trial of an augmented exercise referral scheme using web-based behavioural support for inactive adults with chronic health conditions: the e-coachER trial. Issue 8 (27th November 2020) - Taylor, Adrian; Taylor, Rod S; Ingram, Wendy; Dean, Sarah Gerard; Jolly, Kate; Mutrie, Nanette; Lambert, Jeff; Yardley, Lucy; Streeter, Adam; Greaves, Colin; McAdam, Chloe; Price, Lisa; et al.
Abstract : Objective: To determine whether adding web-based support (e-coachER) to an exercise referral scheme (ERS) increases objectively assessed physical activity (PA). Design: Multicentre trial with participants randomised to usual ERS alone (control) or usual ERS plus e-coachER (intervention). Setting: Primary care and ERS in three UK sites from 2015 to 2018. Participants: 450 inactive ERS referees with chronic health conditions. Interventions: Participants received a pedometer, PA recording sheets and a user guide for the web-based support. e-coachER interactively encouraged the use of the ERS and other PA options. Main outcome measures: Primary and key secondary outcomes were: objective moderate-to-vigorous PA (MVPA) minutes (in ≥10 min bouts and without bouts), respectively, after 12 months. Secondary outcomes were: other accelerometer-derived and self-reported PA measures, ERS attendance, EQ-5D-5L, Hospital Anxiety and Depression Scale and beliefs about PA. All outcomes were collected at baseline, 4 and 12 months. Primary analysis was an intention to treat comparison between intervention and control arms at 12-month follow-up. Results: There was no significant effect of the intervention on weekly MVPA at 12 months between the groups recorded in ≥10 min bouts (mean difference 11.8 min of MVPA, 95% CI: −2.1 to 26.0; p=0.10) or without bouts (mean difference 13.7 min of MVPA, 95% CI: −26.8 to 54.2; p=0.51) for 232 participants with usable data. There was no difference in the primary or secondary PA outcomes at 4 or 12 months. Conclusion: Augmenting ERS referrals with web-based behavioural support had only a weak, non-significant effect on MVPA. Trial registration number: ISRCTN15644451 .